1974
DOI: 10.1128/iai.9.1.159-166.1974
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Serotyping of Three Feline Reovirus Isolates

Abstract: Three feline virus isolates were shown to be members of the reovirus group by their growth characteristics in cell cultures, physicochemical properties, and appearance under an electron microscope. Their close serological relationship to, or identity with, human reovirus type III was revealed by hemagglutination, hemagglutination inhibition, serum neutralization, and gel diffusion tests. One feline isolate (636) was pathogenic for suckling mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, MRV-3 infection has been associated to a case of meningitis in a child (Tyler et al, 2004). The ability to induce neurological disease is a characteristic of MRV-3 and a neurovirulent MRV-3 strain has been isolated from a cat with ataxia (Csiza, 1974). Because of the apparent lack of species barriers, MRVs may potentially spread from animals to humans and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MRV-3 infection has been associated to a case of meningitis in a child (Tyler et al, 2004). The ability to induce neurological disease is a characteristic of MRV-3 and a neurovirulent MRV-3 strain has been isolated from a cat with ataxia (Csiza, 1974). Because of the apparent lack of species barriers, MRVs may potentially spread from animals to humans and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian reoviruses have a wide geographic distribution and can virtually infect all mammals, including humans (Tyler, 2001). In carnivores, MRV infections have been sporadically reported, although all the three serotypes have been isolated from dogs and cats (Binn et al, 1977;Csiza, 1974;Kokubu et al, 1993;Lou and Wenner, 1963;Marshall et al, 1987;Massie and Shaw, 1966;Mochizuki and Uchizono, 1993;Scott et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, 3–6-month-old pigs in the disease outbreak farm in this study were 96% MRV-seropositive, suggesting that MRV outbreak in this farm might be responsible for the severe infections in pigs. Additionally, previous studies have revealed that MRV3 σ1-based indirect ELISA assay can also detect MRV serotype 1 strains [ 55 ] and the feline MRV cross-reacts with three MRV serotypes based on the neutralization testing [ 39 ], suggesting a potential serological cross-reaction among different serotypes of MRVs. Therefore, whether the high sero-prevalence in pigs we found is MRV1-specific or due to cross-reactivity with other serotypes, or due to maternal antibodies needs to be determined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples collected from gnotobiotic, caesarian-derived colostrum-deprived piglets without maternal antibodies, which are MRV negative, were used for the negative control. HI assay was performed as described previously with modifications [ 39 ]. Briefly, 200 µl receptor destroying enzyme (RDE II) (DENKA SEIKEN, Japan) -treated serum was transferred to 96-well microtiter plates and 10 µl of 25% (v/v) swine RBCs collected from MRV-seronegative pigs was added into each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation